2020
DOI: 10.21203/rs.3.rs-56812/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Relevance of Oncogenic Driver Mutations Identified in Endometrial Carcinoma

Abstract: Background: Endometrial carcinoma is a clinically heterogeneous disease characterized by a number of different histological subtypes, and its heterogeneity may be involved in the accumulation of multiple genetic alterations. The aim of this work is to investigate a comprehensive mutational profile of endometrial carcinoma tumors, and examine the correlations with somatic mutations and clinicopathological features or survival in endometrial carcinoma patients. Methods: A total of 100 surgical tumors were obtain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It is the most frequently mutated tumor suppressor gene that negatively impacts the PI3K-AKT signaling pathway, initiating the process of carcinogenesis. 6 As unopposed estrogens promote endometrial proliferation, glands with PTEN loss may undergo clonal expansion and develop endometrial atypia/cancer. Several studies have demonstrated that PTEN is lost as an early event.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most frequently mutated tumor suppressor gene that negatively impacts the PI3K-AKT signaling pathway, initiating the process of carcinogenesis. 6 As unopposed estrogens promote endometrial proliferation, glands with PTEN loss may undergo clonal expansion and develop endometrial atypia/cancer. Several studies have demonstrated that PTEN is lost as an early event.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the frequencies of PTEN , ARID1A , and PIK3CA mutations in G3EEC are higher than those in serous carcinoma 6,12 . Furthermore, the distribution of somatic mutations in cancer‐related genes in Asian patients with G3EEC remains unknown and, because of the rare histological types, validation studies confirming that somatic mutations are associated with clinical outcomes are scant 13,14 . Therefore, the frequency of oncogenic mutations in Japanese patients with G3EEC, as one of the Asian patient subpopulations, needs further clarification, and the association between genomic alteration classification and clinical outcomes requires further verification.…”
Section: Introductionmentioning
confidence: 99%